Relationships of pelagic ciliates with the microbial food web components at a coastal station in the oligotrophic Eastern Mediterranean Sea: temporal and vertical variability. (27th August 2021) - Romano, Filomena; Pitta, Paraskevi
Abstract: The annual/temporal and vertical dynamics of the microbial food web (MFW) was studied in a coastal station of the oligotrophic Eastern Mediterranean Sea. The present study analyzed the changes of all components of the MFW with a specific focus on the relationships between different size classes of heterotrophic and mixotrophic ciliates with their potential prey. The MFW was dominated by heterotrophic picoplankton in all months and depths analyzed, whereas autotrophic nanoplankton took advantage in cold months with higher nutrient availability. On the other hand, mixotrophic microplankton biomass was higher in summer when nutrients and chlorophyll-a were scarce. As part of the mixotrophic biomass, mixotrophic ciliates were correlated with their "potential" prey at the surface and deep chlorophyll maximum. Large mixotrophic ciliates ( L. strobila ) were more selective in terms of potential prey, showing a correlation with Synechococcus . On the other hand, mixotrophic nanociliates ( Strombidium dalum ) were correlated differently with different potential prey according to depth, supporting the idea that nanociliates could be more generalists in terms of prey selection. Because the relationships between mixotrophic ciliates and their potential prey are still poorly studied, this work represents the start for further investigation.